Lipoprotein(a), a Lethal Player in Calcific Aortic Valve Disease - Hu, Jiahui; Lei, Hao; Liu, Leiling; Xu, Danyan (Frontiers in Cell and Developmental Biology, 2022)
Calcified aortic valve disease (CAVD) is the most common valvular cardiovascular disease with increasing incidence and mortality. The primary treatment for CAVD is surgical or transcatheter aortic valve replacement and there remains a lack of effective drug treatment. Recently, lipoprotein (a) (Lp(a)) has been considered to play a crucial role in CAVD pathophysiology. Multiple studies have shown that Lp(a) represents an independent risk factor for CAVD. Moreover, Lp(a) mediates the occurrence and development of CAVD by affecting aortic valve endothelial dysfunction, indirectly promoting foam cell formation through oxidized phospholipids (OxPL), inflammation, oxidative stress, and directly promotes valve calcification. However, there is a lack of clinical trials with Lp(a) reduction as a primary endpoint. This review aims to explore the relationship and mechanism between Lp(a) and CAVD, and focuses on the current drugs that can be used as potential therapeutic targets for CAVD.